2018
DOI: 10.1007/s10151-018-1803-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic pilonidal sinus treatment (EPSiT): a systematic review

Abstract: Initial studies on EPSiT have shown promising results. However, there is a need for a standardised technique and more comparative studies to validate this novel procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 21 publications
1
38
0
3
Order By: Relevance
“…Early post-operative morbidity should be taken into special consideration as it greatly interferes with patients' quality of life, especially when postoperative complications such as dehiscence occur. As many others, this study shows that EPSiT improves psychological state, social function and pain (7, 19, 21, 22). Pit-picking is reported to have the same results, like it was expected, once EPSiT only complements Pit-picking with the endoscopic view (23).…”
Section: Discussionsupporting
confidence: 83%
“…Early post-operative morbidity should be taken into special consideration as it greatly interferes with patients' quality of life, especially when postoperative complications such as dehiscence occur. As many others, this study shows that EPSiT improves psychological state, social function and pain (7, 19, 21, 22). Pit-picking is reported to have the same results, like it was expected, once EPSiT only complements Pit-picking with the endoscopic view (23).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, several recent systematic reviews have analysed EPSiT/VAAPS application from published case series along with the one randomised trial published to date. Tien et al showed patients undergoing EPSiT/VAAPS to have reduced time off work, low short term recurrence and high satisfaction scores although the technique took longer to perform and required specialist, expensive equipment [ 70 ]. Furthermore, Emile et al assessed 497 patients across 9 studies (6 prospective, 2 retrospective and 1 RCT) [ 71 ].…”
Section: The Future Of Pilonidal Sinus Surgery: the Shift Towards Endmentioning
confidence: 99%
“…In zwei systemischen Metaanalysen [161,460], die 8 bzw. 9 Studien aus 6 Zentrenund 497 Patientenbeinhalteten, wurde ein Therapieversagen von 8 % (4 % Rezidive und 4 % persistierende Befunde) berechnet.…”
Section: Endoskopische Verfahrenunclassified